Financial Statement Comparability and Idiosyncratic Return Volatility - Habib, A.; Hasan, Mostafa; Al-Hadi, Ahmed (Wiley-Blackwell Publishing Asia, 2018)
© 2018 International Review of Finance Ltd. 2018 This study examines the association between financial statement comparability and idiosyncratic return volatility (IRV). A greater degree of comparability lowers information acquisition costs, reduces the uncertainties associated with performance evaluation, and increases the overall quantity and quality of information available to corporate outsiders, which, in turn, helps investors to understand and evaluate the cash flow and performance of firms more accurately. Therefore, we hypothesize a negative association between financial statement comparability and IRV. Using a large US sample from 1981 to 2013, we show that financial statement comparability is associated with lower level of IRV significantly. We also find this association to be more pronounced in a poor information environment. This study contributes to the emerging research that stresses the benefits of financial statement comparability.